Developing Midwives’ Role as A Stunting Center at The Village Government Level: A Case Study - Nurlailis Saadah; Sulikah Sulikah; Agung Suharto; Budi Joko Santosa; Budi Yulianto; Syaifoel Hardy (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The handling of stunting at the village level so far cannot be said to be effective due to the absence of prevention centers by healthcare professionals. The objective is to develop the role of the village midwife as a central role for stunting prevention with a clear flow of tasks and responsibilities. The implication of this research will be to emphasize a more structured stunting prevention system. This research used a case study method with a descriptive design. The instrument used for data acquisition was a semi-structured question list through in-depth interviews, supported by document reviews from reputable journals for the last five years (2016-2021). The target of the interview was a village midwife in Trenggalek, East Java. The data analysis was PICO (Population, Intervention, Comparison, Output).  There were 7 themes from the interviews and 8 reputable journals as supporting data for the PICO selection. The analysis concluded that developing the role of midwives in dealing with stunting, required management reform (SOP), increased collaboration between professions and sectors, family economy, and availability of funds. It was recommended that village midwives are the most appropriate health professionals at village-level stunting prevention centers who report to the BKKBN institution. Abstrak: Penanganan stunting di tingkat desa selama ini belum bisa dikatakan efektif karena belum adanya pusat pencegahan oleh tenaga kesehatan. Tujuannya untuk mengembangkan peran bidan desa sebagai peran sentral pencegahan stunting dengan alur tugas dan tanggung jawab yang jelas. Implikasi dari penelitian ini adalah untuk menekankan sistem pencegahan stunting yang lebih terstruktur. Penelitian ini menggunakan metode studi kasus dengan desain deskriptif. Instrumen yang digunakan untuk perolehan data adalah daftar pertanyaan semi terstruktur melalui wawancara mendalam yang didukung dengan telaah dokumen dari jurnal-jurnal bereputasi selama lima tahun terakhir (2016-2021). Sasaran wawancara adalah bidan desa di Trenggalek, Jawa Timur. Analisis data yang digunakan adalah PICO (Population, Intervention, Comparison, Output). Terdapat 7 tema hasil wawancara dan 8 jurnal bereputasi sebagai data pendukung seleksi PICO. Hasil analisis menyimpulkan bahwa untuk mengembangkan peran bidan dalam mengatasi stunting diperlukan reformasi manajemen (SOP), peningkatan kerjasama antar profesi dan sektor, ekonomi keluarga, dan ketersediaan dana. Direkomendasikan agar bidan desa merupakan tenaga kesehatan yang paling tepat di pusat penanggulangan stunting tingkat desa yang melapor kepada lembaga BKKBN